2012
DOI: 10.1371/journal.pone.0031570
|View full text |Cite
|
Sign up to set email alerts
|

Gender Dimorphism in Aspartame-Induced Impairment of Spatial Cognition and Insulin Sensitivity

Abstract: Previous studies have linked aspartame consumption to impaired retention of learned behavior in rodents. Prenatal exposure to aspartame has also been shown to impair odor-associative learning in guinea pigs; and recently, aspartame-fed hyperlipidemic zebrafish exhibited weight gain, hyperglycemia and acute swimming defects. We therefore investigated the effects of chronic lifetime exposure to aspartame, commencing in utero , on changes in blood glucose parameters, spatial learning and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 68 publications
5
70
0
Order By: Relevance
“…Some examples of non-favorable NAS metabolic effects suggested in such models include works by Swithers and colleagues, who demonstrated weight gain in rats following consumption of saccharin, 12,22 acesulfame-potassium (AceK) 22 or stevia, 11 with saccharin also linked to increased adiposity. 12 Increased weight gain in rats consuming saccharin or aspartame was also reported by Bertoluci and colleagues, 23 while aspartame consumption was shown to increase weight gain and adiposity in mice, as reported by Al-Mohanna and colleagues 24 and by Shibata and colleagues, 25 respectively. Rats consuming sucralose were also shown by Schiffman and colleagues 26 to gain more weight, a finding that initiated intense debate.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Some examples of non-favorable NAS metabolic effects suggested in such models include works by Swithers and colleagues, who demonstrated weight gain in rats following consumption of saccharin, 12,22 acesulfame-potassium (AceK) 22 or stevia, 11 with saccharin also linked to increased adiposity. 12 Increased weight gain in rats consuming saccharin or aspartame was also reported by Bertoluci and colleagues, 23 while aspartame consumption was shown to increase weight gain and adiposity in mice, as reported by Al-Mohanna and colleagues 24 and by Shibata and colleagues, 25 respectively. Rats consuming sucralose were also shown by Schiffman and colleagues 26 to gain more weight, a finding that initiated intense debate.…”
Section: Introductionmentioning
confidence: 55%
“…Rats consuming sucralose were also shown by Schiffman and colleagues 26 to gain more weight, a finding that initiated intense debate. 27 In addition to weight gain, both saccharin and aspartame have been associated with impaired glucose homeostasis in mice, 24,28,29 and aspartame was also shown to induce hyperinsulinemia, 25 impaired insulin tolerance 24,28 and worsened atherosclerosis in genetically-susceptible (ApoE ¡/¡ ) mice. 30,31 In contrast, Flatt and colleagues described anti-hyperglycemic and antihyperinsulinemic effects for saccharin in genetically obese (ob/ob) mice, coupled with attenuation of weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Mitsutomi et al [26], examining the impact of exposure to a combination of non-nutritive sweeteners (‘NNS’: 99% erythritol and 1% aspartame) in mature C57BL/6 mice with diet-induced obesity, reported not only dramatically higher epididymal white tissue mass in the NNS-exposed group – despite comparable food intake – but also insulin levels that were double those in a plain-water control group [26]. Similarly, in 2012 Collison et al, studying C57BL/6J mouse offspring exposed to aspartame from conception through age 17 weeks, reported that aspartame exposure increased percent weight gain and reduced insulin sensitivity in males, and markedly increased visceral fat and fasting glucose in both sexes, even in the absence of increased weight gain in females [35]. In a second experiment also published in 2012, Collison et al [25] reported significantly increased percent weight change in males – but not females – exposed to either ASP alone or the combination of ASP + MSG [25].…”
Section: Results From Animal Studiesmentioning
confidence: 99%
“…Two-thirds of RCTs reviewed by Miller et al [38], however, had included either disproportionately few [3946] or no males [4750], even though animal studies have shown greater weight gain following LCS exposure in males, compared with females [19,35]. Similarly, ethnic minorities – such as African Americans and Mexican Americans – and lower-income participants have typically been underrepresented in RCTs, even though obesity and diabetes prevalence is higher in these groups [5153].…”
Section: Lessons From Animal Studies and Their Relevance To The Dmentioning
confidence: 99%
“…In contrary, this research also mentioned that aspartame acted as a chemical stressor and raised oxidative stress leading to inflammation (Choudhary and Devi 2015). Other studies also demonstrated that aspartame consumption could cause an increment of fat and body mass (Collison et al, 2012;Feijo et al, 2013), liver damage, and non-alcoholic fatty liver disease (NAFLD) (Abhilash et al, 2011). A study by Yang (2010) proposed that the sweet response produced after consuming artificial sweetener could increase the appetite and reduce satiety, which finally led to obesity development.…”
Section: Introductionmentioning
confidence: 89%